Creative and collaborative reflective thinking to support policy deliberation and decision making. (15th May 2022) - Spaa, Anne; Spencer, Nick; Durrant, Abigail; Vines, John
Abstract : Background: Co-creation in policymaking is of increasing interest to national governments, and designers play a significant role in its introduction. Aims and objectives: We discuss instances from our fieldwork that demonstrated how UK Policy Lab used design methods to gain insight into the design-oriented methods introduced to policymakers' practices, and how these may influence conventional policy design processes. Methods: This paper reports on the learnings from a two-month participant observation at UK Policy Lab conducted in early 2019. Findings: We found that, beyond human-centred and future-oriented practices, the designers working at this unit appropriate design as a reflective practice for the context of policymaking. We discuss how the use of visual and creative methods of design are utilised by policy designers to facilitate co-creative reflective practices, and how these make a valuable contribution to policymaking practices in UK Government. Discussion and conclusions: As deliberation and decision making is influenced both by what is thought about as well as who is doing the thinking, reflective practices allow notions and assumptions to be unpicked. Moreover, when done as a group activity, reflection leads to a co-production of a deepened understanding of policy challenges. Consequently, we argue, the reflective practices introduced by Policy Lab are an essential contribution to developing a co-creation tradition in evidence-informed policymaking processes.